Early Inflammatory Markers for the Diagnosis of Late-Onset Sepsis in Neonates: The Nosodiag Study - Dillenseger, Laurence; Langlet, Claire; Iacobelli, Silvia; Lavaux, Thomas; Ratomponirina, Charline; Labenne, Marc; Astruc, Dominique; Severac, François; Gouyon, Jean Bernard; Kuhn, Pierre (Frontiers in Pediatrics, 2018)
Background: Early diagnosis is essential to improve the treatment and prognosis of newborn infants with nosocomial bacterial infections. Although cytokines and procalcitonin (PCT) have been evaluated as early inflammatory markers, their diagnostic properties have rarely been compared. Objectives: This study evaluated and compared the ability of individual inflammatory markers available for clinician (PCT, semi-quantitative determination of IL8) and of combinations of markers (CRP plus IL6 or quantitative or semi-quantitative determination of IL8) to diagnose bacterial nosocomial infections in neonates. Methods: This prospective two-center study included neonates suspected of nosocomial infections from September 2008 to January 2012. Inflammatory markers were measured initially upon suspicion of nosocomial infection, and CRP was again measured 12–24 hours later. Newborns were retrospectively classified into two groups: those who were infected (certainly or probably) and uninfected (certainly or probably). Results: The study included 130 infants of median gestational age 28 weeks (range, 24–41 weeks). Of these, 34 were classified as infected and 96 as uninfected. The sensitivity, specificity, positive and negative predictive values (PPV and NPV), and positive and negative likelihood ratios (LR+ and LR-) for PCT were 59.3% (95% confidence interval [CI], 38.8–77.6%), 78.5% (95% CI, 67.8–86.9%), 48.5% (95% CI, 30.8–66.5%), 84.9% (95% CI, 74.6–92.2%), 2.7 (95% CI, 1.6–4.9), and 0.5 (95% CI, 0.3–0.8), respectively. Semi-quantitative IL8 had the highest specificity (92.19%; 95% CI, 82.70–97.41%), PPV (72.22%; 95% CI, 46.52–90.30%) and LR+ (6.17, 95% CI, 2.67–28.44), but had low specificity (48.15%; 95% CI, 28.67–68.05%). Of all markers tested, the combination of IL6 and CRP had the highest sensitivity (78.12%; 95% CI, 60.03–90.72%), NPV (91.3%; 95% CI, 82.38–96.32%) and LR- (0.29; 95% CI, 0.12–0.49). The combination of IL-6 and CRPi had a higher area under the curve than PCT, but with borderline significance (p = 0.055). Conclusions: The combination of IL-6 and CRPi was superior to other methods, including PCT, for the early diagnosis of nosocomial infection in neonates, but was not sufficient for sole use. The semi-quantitative determination of IL-8 had good diagnostic properties but its sensitivity was too low for use in clinical practice.